Study on the interaction mechanism in the hardening process of cement-asphalt mortar. (10th December 2019) - Sun, Huadong; Ding, Yongling; Jiang, Peng; Wang, Baoqun; Zhang, Aiqin; Wang, Deming
Highlights: Type of emulsified asphalt affected ionic strength and pH value of CA mortar. Four components were firstly separated from asphalt and researched for interfacial reaction. The adsorption behavior mainly occurred in the asphaltene and resin components of asphalt. There was a chemical adsorption process between asphalt components and cement. Abstract: As an inorganic-organic composite, cement asphalt mortar (CA mortar) is a crucial material for ballastless track structure, integrating cement mechanical properties and asphalt flexibility. Therefore, as a semi-flexible pavement material, it has extensive application in high-speed railways. To ascertain interfacial behavior during the hardening process of CA mortar, the interaction mechanism was investigated by measurement of the electrical conductivity, pH values, relative adsorption rate, and Fourier transform infrared (FT-IR) spectroscopy. Cement hydration process and the type of emulsified asphalt can affect ionic strength and pH value of the slurry system. The results indicated that the cement hydration process was beneficial to the enhancement of electrical conductivity because of an increase in the amount of ions released in the system. By contrast, anionic emulsifier, cationic emulsifiers performed better in improving electrical properties and had higher electrical conductivity. The addition of emulsified asphalts led to the delays of the cement hydration. The reaction mechanism involving the retardation effect mainly owed to the combination of emulsifier with cement particles at the active sites through the acid-base neutralization reaction. Hence, anionic emulsified asphalt exhibited a positive impact on cement hydration and displayed a high pH value. To further confirm the bonding performance of asphalt binder via identifying the functional chemical group, four components were firstly separated from asphalt. In respect to four components of asphalt, the adsorption behavior mainly occurred in the asphaltene and resin components, attributing to the strong chemical bonding effect, which was confirmed by the results of infrared spectra.